GUS assay in hypocotyl generated callus of chili (Capsicum annuum L.) cultivar Kashi Anmol - Prasad, Indivar; Pandey, Himanshu; Krishna, Ram; Singh, Achuit K.; Kumar, Rajesh (Vegetable Science, 2025)
.